To the dialogue of poetry and philosophy: religious and philosophical context of the formation of the “word – logos” acmeist concept - Кихней, Любовь; Меркель, Елена (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
The article considers the regularities of Osip Mandelshtam’s poetical semantics through philosophical and aesthetic ideas about the word of religious thinkers and the poet himself. The paper demonstrates the correspondence of principles of Mandelshtam’s poetic semantics with his linguistic and philosophical picture of the world. The regularities and fundamental principles of Mandelshtam’s poetic semantics have been revealed.